2010
DOI: 10.5772/10495
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Kinematics and Control of a 7-DOF Redundant Manipulator Based on the Closed-Loop Algorithm

Abstract: Closed-loop inverse kinematics (CLIK) algorithm mostly resolves the redundancy at the velocity level. In this paper we extend the CLIK algorithm to the acceleration level to meet some applications that require the joint accelerations. The redundancy resolutions at the velocities and acceleration levels via pseudoinverse method are analyzed respectively. The objective function of joint limits avoidance(JLA) is combined into the redundancy resolution as an optimization approach of the null space motion. A seven-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 20 publications
0
81
0
2
Order By: Relevance
“…is the end-effector velocity and m R q ∈  is the joint velocity [14,15,16,20]. Therefore, we can obtain the velocity inverse kinematics through the generalize inverse Jacobian matrix method as follows:…”
Section: Obstacle Avoidance Of Redundant Manipulators Based On Gradiementioning
confidence: 99%
“…is the end-effector velocity and m R q ∈  is the joint velocity [14,15,16,20]. Therefore, we can obtain the velocity inverse kinematics through the generalize inverse Jacobian matrix method as follows:…”
Section: Obstacle Avoidance Of Redundant Manipulators Based On Gradiementioning
confidence: 99%
“…where 2 Eqs. (8)- (12) show that for any point p E = x E y E z E γ β T given in the workspace, we can determine the value of q analytically.…”
Section: Inverse Kinematics Analysismentioning
confidence: 99%
“…Further studies in this area can be found in the literature, such as the kinematics design of manipulators [1], the kinematics of the redundant robot [2], the kinematics of the parallel robot [3,4]. There is much research in the area of the modelling and design of serial manipulators carrying heavy payloads [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Redundancy resolution in velocity making use of pseudo-inverse approaches has been widely used in various subtask controls such as singularity avoidance (Yoshikawa, 1984), joint velocity minimization (Seraji, 1991), obstacle avoidance (Chen et al, 2002), mechanical joint limit avoidance (Tatlıcıoğlu et al, 2009), and manipulability (Maaroof et al, 2012). In addition, different redundancy resolution approaches have been proposed including in velocity level (Rajiv et al, 1991) and in acceleration level (Wang et al, 2010). Examples presented above address optimization for var-ious sub-tasks.…”
Section: Introductionmentioning
confidence: 99%